Kebutuhan dan Peluang Pengembangan Fasilitas Pedestrian Pada Sistem Jalan di Perkotaan - B. S. Kusbiantoro; Petrus Natalivan; Dian Aquarita (Journal of Regional and City Planning, 2007)
This article is aimed at explaining the relation between urban road system and need and possibility for the development of pedestrian facilities. Literature review is conducted to formulate need and possibility for the development of pedestrian facilities. Empirical study is conducted to structure the problems of the development of pedestrian facilities, to identify the need based on the existing road system, and to formulate the possibility in the future. The results show us that the need for the development of pedestrian facilities based on the existing road system can be identified based on road functions, road network pattern, and mobility pattern. Based on these criteria, pedestrian facilities on the road system of Bandung Municipality are highly needed. However, the large space needed for pedestrian facilities and limited dimension of the right of ways (ROW) cause the limited space available for the development of pedestrian facilities. There are only several row of road on which pedestrian facilities can he optimally developed. The rests are restricted only for the main pedestrian facilities. Moreover, they have no possibility to be developed for pedestrian facilities because the roadsides are small Although the urban road system meets the criteria for the development of pedestrian facilities, ills not guaranteed that the pedestrian facilities are developed on it. This is because motive and perception towards the mode of walking also influence the development decision.